2019
DOI: 10.1128/aac.00512-19
|View full text |Cite
|
Sign up to set email alerts
|

Amphotericin B Induction with Voriconazole Consolidation as Salvage Therapy for FKS -Associated Echinocandin Resistance in Candida glabrata Septic Arthritis and Osteomyelitis

Abstract: We report the case of a 61-year-old female with Crohn’s disease dependent on total parenteral nutrition who developed a central venous catheter bloodstream infection and septic arthritis, complicated further by osteomyelitis and persistent Candida glabrata fungemia. Fluconazole treatment led to persistent infection, and micafungin therapy failed with development of FKS-associated resistance. Infection responded after initiation of amphotericin B plus voriconazole. Echinocandin resistance is increasingly recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
5
8
0
Order By: Relevance
“…In our case, taking advantage of morphologically different C. glabrata colonies [51] from the patient's blood culture that yielded isolate 2, we were able to detect echinocandin resistance by testing more than one colony. Consistent with recent studies [16,26], we found that isolate 2 harbored the FKS2 HS1 F659Y. In a two-year antifungal resistance surveillance study [16], 8 (15.7%) of 51 C. glabrata isolates with FKS HS alterations harbored the FKS2 HS1 F659S/V/Y [25,52], which was the second found after the FKS2 HS1 S663P (16 isolates).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our case, taking advantage of morphologically different C. glabrata colonies [51] from the patient's blood culture that yielded isolate 2, we were able to detect echinocandin resistance by testing more than one colony. Consistent with recent studies [16,26], we found that isolate 2 harbored the FKS2 HS1 F659Y. In a two-year antifungal resistance surveillance study [16], 8 (15.7%) of 51 C. glabrata isolates with FKS HS alterations harbored the FKS2 HS1 F659S/V/Y [25,52], which was the second found after the FKS2 HS1 S663P (16 isolates).…”
Section: Discussionsupporting
confidence: 90%
“…We provided the evidence of an in vivo development of FKS-associated echinocandin resistance during the patient's treatment with caspofungin, consistent with previous case reports [26,39,40]. In two of them, echinocandin-resistant isolates were recovered from blood cultures of patients who had recurrent or persistent C. glabrata infections, thus implying micafungin treatments for 86 days in one case [26] and 30 days in the other case [39]. In another one [40], echinocandin resistance emerged within 8 days of the patient's treatment with micafungin, and surprisingly, the patient had no previous or prolonged echinocandin exposure [41], but only uncontrolled diabetes, as a potential risk factor for microbiological failure.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Candida glabrata is the second leading cause of candidaemia in USA, 1 Canada, 2 Australia 3 and some Scandinavian countries 4‐9 and the first cause of candidaemia in intensive care units and patients with haematological malignancies and solid tumours 10,11 . Compared to the other Candida species, C glabrata is much more tolerant to antifungals, 12 which allows it to rapidly develop antifungal resistance during the course of antifungal therapy 13‐22 . Indeed, C glabrata isolates resistant to azoles or echinocandins and even those demonstrating multidrug resistance are increasingly being identified in clinical settings 6,8,23 .…”
Section: Introductionmentioning
confidence: 99%